Synapses and Dendritic Spines as Pathogenic Targets in Alzheimer’s Disease - Wendou Yu; Bingwei Lu (Neural Plasticity)
Synapses are sites of cell-cell contacts that transmit electrical or chemical signals in the brain. Dendritic spines are protrusions on dendritic shaft where excitatory synapses are located. Synapses and dendritic spines are dynamic structures whose plasticity is thought to underlie learning and memory. No wonder neurobiologists are intensively studying mechanisms governing the structural and functional plasticity of synapses and dendritic spines in an effort to understand and eventually treat neurological disorders manifesting learning and memory deficits. One of the best-studied brain disorders that prominently feature synaptic and dendritic spine pathology is Alzheimer’s disease (AD). Recent studies have revealed molecular mechanisms underlying the synapse and spine pathology in AD, including a role for mislocalized tau in the postsynaptic compartment. Synaptic and dendritic spine pathology is also observed in other neurodegenerative disease. It is possible that some common pathogenic mechanisms may underlie the synaptic and dendritic spine pathology in neurodegenerative diseases.